Otorhinolaryngology: textbook - Пальчун, В. Т. оториноларингология 19290427 Владимир Тимофеевич (Textbook, 2020)
The textbook provides a brief introduction to the fundamental basics of etiology, pathogenesis, diagnosis and treatment of upper respiratory tract and ear diseases, as well as the latest scientific and practical information in this field. Updated materials on endonasal microendoscopic diagnostics and surgery are included. Modern rationale for methods of choice in diagnostics and treatment of the main ENT organ diseases are presented, generalizing data on the use of drugs is given. Becoming more common lesions of ENT organs in HIV infection, Wegener's disease, tuberculosis, sexually transmitted diseases and etc. are described. The issues of urgent conditions in the specialty are covered. The textbook is intended for students of medical universities, interns, residents, postgraduates.